2009
DOI: 10.1037/a0015331
|View full text |Cite
|
Sign up to set email alerts
|

The cost of search for multiple targets: Effects of practice and target similarity.

Abstract: With the use of X-ray images, performance in the simultaneous search for two target categories was compared with performance in two independent searches, one for each category. In all cases, displays contained one target at most. Dual-target search, for both categories simultaneously, produced a cost in accuracy, although the magnitude of this dual-target cost was affected by the nature of the targets. When target feature sets shared values, accuracy in dual-target search was equivalent to that in the less acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
154
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(173 citation statements)
references
References 34 publications
16
154
3
Order By: Relevance
“…did participants perform the dual-target search first, second or third, Figure 10 targets respectively). However, previous work has shown that the dual-target cost remains even after extensive practice (Menneer et al, 2009;Menneer et al, 2012). In the current experiments, perhaps the shedding of non-preferred unfamiliar face target is ameliorated, though not removed, by dedicated prior practice with the same faces appearing as single targets before performing the dual-target search.…”
Section: Dual-target Absent Ratiomentioning
confidence: 70%
See 1 more Smart Citation
“…did participants perform the dual-target search first, second or third, Figure 10 targets respectively). However, previous work has shown that the dual-target cost remains even after extensive practice (Menneer et al, 2009;Menneer et al, 2012). In the current experiments, perhaps the shedding of non-preferred unfamiliar face target is ameliorated, though not removed, by dedicated prior practice with the same faces appearing as single targets before performing the dual-target search.…”
Section: Dual-target Absent Ratiomentioning
confidence: 70%
“…The dual-target cost is found for simple as well as more complex stimuli and persists even after practice (Menneer, Cave, & Donnelly, 2009). In some circumstances, such as when searching for colour targets, overall speed decreases and accuracy falls when searching for two targets compared with single-target search, but both targets can be found with accuracy levels above chance.…”
Section: Dual-target Cost In Visual Search For Multiple Unfamiliar Facesmentioning
confidence: 99%
“…Modelling of these behavioural results suggested that exactly one attentional template can be active at any given time (see also Meneer, Cave, &Donnelly, 2009, andStroud et al, 2011, for additional behavioural evidence, and , for ERP evidence that attentional target selectivity is less effective during multiple-colour as compared to single-colour visual search). If attentional templates are working memory representations, and if working memory can hold several objects simultaneously, why should only a single search template be active at a time?…”
Section: Preparatory Attentional Templates and Visual Working Memorymentioning
confidence: 99%
“…Given that such switch costs necessary to search through visual working memory require time (taking up to 300 -500 ms, Garavan, 1998, see also Oberauer, 2002 and there is a dual task cost of searching through multiple targets (e.g. Godwin et al, 2010, Menneer et al, 2007Menneer et al, 2009;Menneer et al 2010) people may instead chose a heuristic to more willingly trust CAD rather than search through the many possible target representations in Visual Working Memory. This led to good search when the CAD cue was correct, but inaccurate search when the CAD cue was wrong.…”
Section: Visual Working Memory and Cadmentioning
confidence: 99%
“…However, searching for multiple targets simultaneously has been shown to lead to dualtarget costs where response times are slower and accuracy falls (e.g. , Menneer, Barrett, Phillips, Donnelly & Cave, 2007Menneer, Cave, & Donnelly, 2009;. Mestry et al (2016) suggested that the reason for this decline in accuracy is that when searching for two possible targets, one of the targets becomes classified as the non-preferred target and is 'shed' (i.e., participants give up searching for the non-preferred target in favour of the preferred one).…”
Section: Introductionmentioning
confidence: 99%